Answer:
The pairs (12,0) , (3,-1) and (0,-4/3) make the equation x- 9 y = 12 TRUE.
Explanation:
Here, the given equation is x - 9 y = 12
Checking for each pairs individually:
a) For (12,0):
x - 9y = (12) - 9(0) = 12
and 12 = 12 (Right Side).
Hence, (12,0) satisfies the equation.
b) For (0,12):
x - 9y = 0 - 9(12) = -118
and -118 ≠ 12 (Right Side).
Hence,(0,12) DO NOT satisfy the equation.
c) For (3,-1):
x - 9y = 3 - 9((-1) ) = 3 + 9 = 12
and 12 = 12 (Right Side).
Hence, (3,-1) satisfies the equation.
d) For (0,-4/3):
x - 9y = 0 - 9((-4/3) ) = 0 + 12 = 12
and 12 = 12 (Right Side).
Hence, (0,-4/3) satisfies the equation.
Hence, the pairs (12,0) , (3,-1) and (0,-4/3) make the equation x- 9 y = 12 TRUE.